The physiocracy: political and socioeconomic doctrine dominant in 18th century France - DE MEYERE, Pieter (Annals of Spiru Haret University. Economic Series, 2016)
In France the XVIIIth century was characterized by the Enlightenment as a philosophical phenomenon and Physiocracy as an expression of new economic thinking. But the Physiocrats were not merely a school of economic thought, they were also a school of political action. Kings, princes and high public servants were among their pupils. The great French Revolution itself was influenced by their writings. And the force of their work is still not fully spent. In order to appreciate the theory and significance of the Physiocracy it is necessary to take into account the circumstances of its time. Physiocracy is a doctrine which esteems that agriculture is of more importance than industry and commerce. In the above article the following subjects of the physiocratic doctrine are dealt with: the natural order, property and liberty; the relations between the government and the individual citizen, the theory of the produit net and the Tableau Économique of François Quesnay. The evaluation also includes the question about the expansion of Physiocracy. Indeed, it had many followers in several countries of Europe and was also the first real School of economic thinking. By its systematic approach, Physiocracy established the economy as a science. All the aspects of Physiocracy which have been mentioned above are intimately bound together and are in several aspects the economic precursor of the French Revolution.